Analisa Pengaruh Net Working Capital dan Net Sales Terhadap Earning Before Interest and Tax (EBIT) Pada PT Indofood Sukses Makmur Tbk - Burhanuddin Bani (JEM Jurnal Ekonomi dan Manajemen, 2022)
In the era of the Covid-19 Pandemic, many companies have experienced an impact on company life starting with low sales turnover for the trading business. The use of capital also needs to be considered so that it does not become inefficient in generating sales which ultimately leads to operating profit. The picture of profit growth cannot be separated from the company's performance as reflected in the company's finances which is reflected in the summary of the financial statements. This study aims to analyze the effect of net working capital and net sales on earnings before interest and taxes (EBIT). The research sample is the Financial Summary of PT Indofood Sukses Makmur Tbk for the 2016-2020 period. Multiple regression analysis is used to process data with the help of computer programming applications. The test results show that Net Working Capital has no significant effect on EBIT at PT Indofood Sukses Makmur Tbk, while Net Sales has a significant effect on EBIT at PT Indofood Sukses Makmur Tbk. This shows that for certain types of business, not all increases in the use of net working capital affect the increase in operating profit.